Quantitative determination of microcracks on ceramic coatings by means of computer image analysis - (:unkn) unknown (CROATIAN METALLURGICAL SOC, 2005)
In this study, composite and metallic powder is coated on steel, cast iron and aluminium surfaces using flame spray and plasma spray under atmospheric conditions. Surface morphologies have been investigated in detail using Scanning Electron Microscope (SEM). Studies using SEM have illustrated that micro-cracks occur in structures of composite and metallic coatings independently from coating and process parameters. Using segmentation through threshold techniques, amount of microcracks from the point of view quantitative analysis is computed on digital images of microcracks.
Keywords: quantitative analysis; microcracks; metallic and ceramic composites; powder coatings; MECHANICAL-PROPERTIES